"I am not dead yet!" – The Item responds to Hulleman & Olivers. (2017) - Wolfe, Jeremy M.
Abstract: The item can only be dispensed within artificial tasks that, although useful in the lab, do not reflect the real world. There, the attended item is the goal of search. Hulleman & Olivers' (H&O's) model can ignore the item only by reducing search to the question of whether a patch of 0s (distractors) contains a 1 (target).